Factors Influencing Neonatal Mortality Rate in High-Risk Hospital Settings (Northern International Medical College Journal, 2025)
Background: Neonatal mortality remains a significant public health concern in low-resource, hospital settings. Objective: This study aimed to investigate factors influencing neonatal mortality in a tertiary care hospital in Bangladesh, focusing on demographic, maternal, and clinical characteristics associated with neonatal outcomes. Methods: This retrospective study was conducted over one year (January to December 2022) at Bangladesh Shishu Hospital and Institute, involving 2,700 high-risk neonates admitted to the SCABU 1 and SCABU 2. Among these, 216 neonates (8%) died. Data on demographic information, clinical diagnoses, and maternal health factors were collected from hospital records, with statistical analyses performed to identify key mortality risk factors. Results: The primary causes of neonatal mortality were prematurity with its complications (43.98%), sepsis (22.22%), and perinatal asphyxia (10.19%), with 25% of neonates classified as extremely low birth weight (ELBW) (